Renal involvement in AA amyloidosis: A single-center experience with clinical and histopathological data (Annals of Medical Research, 2022)
Aim: We aimed to evaluate clinicopathological features in patients with renal amyloid A (AA) amyloidosis to analyze the impact of renal biopsy on renal and patient outcomes.Materials and Methods: We retrospectively collected data regarding baseline and follow-up clinical and laboratory features. The same pathologist scored each kidney biopsy specimen according to amyloid distrubition and amount with tubulointerstitial findings. We added all scores and obtained renal amyloid prognostic score (RAPS) and then divided patients into three RAPS grades (RAPS grade I, II, III).Results: Eighteen patients (male, 72.2%) with a median age of 51.5 (IQR, 45-58.3) years were included in the study. The most common disease related to AA amyloidosis was previous tuberculosis (33.3%). Median serum creatinine of patients at renal biopsy time was 1.61 (IQR, 0.91-2.89) mg/dL with a median 24-h protein excretion, 6.8 [IQR, 4.6-8.9] g/day. 100%, 94.4%, 55.6% of patients’ renal biopsies had vascular, glomerular (mostly diffuse mesangiocapillary) and interstitial amyloid depositions. RAPS grade I, II and III were detected in 5.6%, 27.8% and 66.7% of the patients, respectively. Ten patients (55.5%) reached end-stage renal disease (ESRD) at a median time of 15 (IQR, 2.3-32.3) months post-biopsy. ESRD was correlated with interstitial fibrosis/tubular atrophy (r=0.608, P= 0.01). Death-censored renal survival rates at 1,3 and 5 years were 83.3%, 58.7% and 43.5%, respectively. Six patients (33.3%) died. Patient survival rates at 1,3 and 5 years were 88.9%, 69.6 and 55.7%, respectively.Conclusion: Early diagnosis of AA amyloidosis with renal biopsy and scoring biopsy specimen according to amyloid distribution with other histopathological findings may be useful to manage the disease and predict the prognosis.
Keywords: Renal biopsy; AA amyloidosis; End-stage renal disease